Analysis of the Calculation of Profit Volume Costs, Break Even Points, Margin of Safety, and Contribution Margin on Profit Planning - Elidawati Elidawati; Edy Terdjo (Indonesian Economic Review, 2026)
The rapid growth of the coffee shop industry in Indonesia has transformed coffee shops into a "third place" for people's lifestyles. However, external pressures during the pandemic caused Coffee Shop X to fail in achieving its 2025 profit target due to operational restrictions. This study aims to evaluate the effectiveness of Cost-Volume-Profit (CVP) analysis as a strategic instrument in profit planning for 2026 to recover financial performance post-contraction. The research method employed is quantitative, utilizing the Least Square method to separate semi-variable costs. The results indicate that the company has a weighted-average contribution margin of IDR 11,256, with a Break-Even Point (BEP) of 19,413 units. To offset the losses incurred in 2025, the company has set a sales target of 29,094 units for 2026. Risk analysis reveals a Margin of Safety of 49.86% and a Degree of Operating Leverage of 4.5, indicating high profit sensitivity to changes in sales volume. In conclusion, CVP analysis provides an accurate foundation for MSME management in formulating profit planning strategies and mitigating operational risks more scientifically in the future.